PERAN KOMUNIKASI INTERPERSONAL PASANGAN SUAMI ISTRI DALAM KEHARMONISAN KELUARGA - Kholifah Jinan; Widya Lestari; Nur Kur'ani (Jurnal Keperawatan dan Kesehatan, 2026)
Background: A harmonious family is an important indicator of well-being in family life. The roles of husbands and wives are essential in achieving family harmony; however, many couples still encounter challenges due to ineffective interpersonal communication. Previous studies have shown that effective interpersonal communication can strengthen relationships and improve family harmony. Objective: To examine the relationship between spousal interpersonal communication and family harmony in Sungai Raya District. Methods: This study employed a quantitative correlational design involving 100 married couples selected from Sungai Raya District. Data were collected using the Interpersonal Communication Scale and the Family Harmony Scale. Statistical analysis was performed using Pearson’s Product Moment correlation test with SPSS software. Results: The results showed a strong positive correlation between interpersonal communication and family harmony (r = 0.859; p = 0.000 < 0.05). This indicates that better interpersonal communication is associated with higher levels of family harmony. Conclusion: Interpersonal communication plays a significant role in fostering family harmony among married couples. Strengthening communication skills between spouses may contribute to improved family well-being.